2020
DOI: 10.1111/tbed.13487
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing milk from pooling facilities as a novel approach for foot‐and‐mouth disease surveillance

Abstract: This study investigated the potential of pooled milk as an alternative sample type for foot‐and‐mouth disease (FMD) surveillance. Real‐time RT‐PCR (rRT‐PCR) results of pooled milk samples collected weekly from five pooling facilities in Nakuru County, Kenya, were compared with half‐month reports of household‐level incidence of FMD. These periodic cross‐sectional surveys of smallholder farmers were powered to detect a threshold household‐level FMD incidence of 2.5% and collected information on trends in milk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Combining the surveillance for FMD with those for other major livestock diseases will reduce the total number of samples to be taken and the associated costs [ 46 ]. When rRT-PCR is available, non-invasive sampling methods such as the collection of pooled milk samples from cattle [ 47 ], pooled oral swabs from sheep, or saliva collected from pigs via ropes have the potential to be a cost-effective alternative or complementary method to traditional serological surveys [ 48 ]. With appropriate enrichment strategies, it is possible to sequence the virus when it is present in low abundance in such samples [ 49 ], illustrating the potential for sequence-based surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the surveillance for FMD with those for other major livestock diseases will reduce the total number of samples to be taken and the associated costs [ 46 ]. When rRT-PCR is available, non-invasive sampling methods such as the collection of pooled milk samples from cattle [ 47 ], pooled oral swabs from sheep, or saliva collected from pigs via ropes have the potential to be a cost-effective alternative or complementary method to traditional serological surveys [ 48 ]. With appropriate enrichment strategies, it is possible to sequence the virus when it is present in low abundance in such samples [ 49 ], illustrating the potential for sequence-based surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The sample content determination does not need to open the reaction tube, and can be analyzed by the fluorescence signal intensity generated during the qRT-PCR amplification process, avoiding cross-contamination between samples ( Galluzzi et al, 2018 ). qRT-PCR has the advantages of rapidity and sensitivity, and is suitable for different clinical sample types including swabs, sera, vesicular fluid, milk and tissue samples ( Burkhalter and Savage, 2017 ; Fontel et al, 2019 ; Yeo et al, 2020 ; Armson et al, 2020a ). At present, Real-Time PCR is a commonly used method to detect the pathogens of animal diseases.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…One study showed that EDTA-stabilized blood samples can be adapted to FMDV detection during FMD outbreak even though the sensitivity of it was 10-fold less than that of serum samples ( Fontel et al, 2019 ). Armson et al determined the utility of testing pooled milk by rRT-PCR as an alternative approach for FMD surveillance, and proved that pooled milk has potential value as a surveillance sample to reveal subclinical FMD infection ( Armson et al, 2020a , b ). Yeo et al amplified the FMDV genomic sequence in meat juice using qRT-PCR and confirmed the presence of FMDV RNA ( Yeo et al, 2020 ).…”
Section: Diagnostic Methodsmentioning
confidence: 99%